Georg Schmorl prize of the German spine society (DWG) 2022: current treatment for inpatients with osteoporotic thoracolumbar fractures—results of the EOFTT study - Ullrich, Bernhard W.; Schenk, Philipp; Scheyerer, Max J.; Bäumlein, Martin; Katscher, Sebastian; Schnake, Klaus J.; Zimmermann, Volker; Schwarz, Falko; Schmeiser, Gregor; Scherer, Michael; Müller, Michael; Sprengel, Kai; et al. (European Spine Journal, 2023)
Aim: Osteoporotic thoracolumbar fractures are of increasing importance. To identify the optimal treatment strategy this multicentre prospective cohort study was performed. Purpose: Patients suffering from osteoporotic thoracolumbar fractures were included. Excluded were tumour diseases, infections and limb fractures. Age, sex, trauma mechanism, OF classification, OF-score, treatment strategy, pain condition and mobilization were analysed. Methods: A total of 518 patients’ aged 75 ± 10 (41–97) years were included in 17 centre. A total of 174 patients were treated conservatively, and 344 were treated surgically, of whom 310 (90%) received minimally invasive treatment. An increase in the OF classification was associated with an increase in both the likelihood of surgery and the surgical invasiveness. Results: Five (3%) complications occurred during conservative treatment, and 46 (13%) occurred in the surgically treated patients. 4 surgical site infections and 2 mechanical failures requested revision surgery. At discharge pain improved significantly from a visual analogue scale score of 7.7 (surgical) and 6.0 (conservative) to a score of 4 in both groups (p < 0.001). Over the course of treatment, mobility improved significantly (p = 0.001), with a significantly stronger (p = 0.007) improvement in the surgically treated patients. Conclusion: Fracture severity according to the OF classification is significantly correlated with higher surgery rates and higher invasiveness of surgery. The most commonly used surgical strategy was minimally invasive short-segmental hybrid stabilization followed by kyphoplasty/vertebroplasty. Despite the worse clinical conditions of the surgically treated patients both conservative and surgical treatment led to an improved pain situation and mobility during the inpatient stay to nearly the same level for both treatments.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Fracture; Osteoporotic; Short-segmental-stabilization; Thoracolumbar; Treatment